2023
DOI: 10.3390/agronomy13092306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Tillage and Residue Retention Measures on Silage Maize Yield and Quality and Soil Phosphorus in Karst Areas

Tao Wang,
Wei Ren,
Feng Yang
et al.

Abstract: Soil phosphorus (P) limitation in karst areas has severely constrained soil quality and land productivity. To enhance silage maize yield and quality and alleviate and/or balance the low phosphorus availability in the karst areas of China, the experiment investigated the effects of different tillage and residue retention practices on silage maize yield and quality and soil phosphorus in this region. The treatment set included: conventional tillage (CT), conventional tillage and root stubble retention (CTH), con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…With several factors interacting and crop yields varying from year to year under the influence of meteorological factors, it is difficult to objectively evaluate the effectiveness of soil tillage methods [74] or other factors involved when using technology. Wang et al [75] found that, although unconventional soil tillage systems do not play a significant role in improving yield, the benefits of the systems on soil health are still evident [76][77][78]. Optimal temperature ratios and water availability allow for the maximum yield to be obtained.…”
Section: Maize Yields Obtained In Relation To the Experimental Factorsmentioning
confidence: 99%
“…With several factors interacting and crop yields varying from year to year under the influence of meteorological factors, it is difficult to objectively evaluate the effectiveness of soil tillage methods [74] or other factors involved when using technology. Wang et al [75] found that, although unconventional soil tillage systems do not play a significant role in improving yield, the benefits of the systems on soil health are still evident [76][77][78]. Optimal temperature ratios and water availability allow for the maximum yield to be obtained.…”
Section: Maize Yields Obtained In Relation To the Experimental Factorsmentioning
confidence: 99%
“…Furthermore, it was determined in previous studies that incorporating straw mulching with these tillage practices had multiple benefits. It improved soil quality and nutrients while also significantly reducing surface runoff volume [10][11][12]. This effect was particularly noticeable when tillage practices were combined with straw mulching, resulting in decreased outflow concentrations and reduced volumes of large-size colloids in surface and subsurface runoff.…”
Section: Introductionmentioning
confidence: 99%